Electrical resistivity monitoring of river–groundwater interactions in a Chalk river and neighbouring riparian zone. Issue 4 (9th July 2020) - McLachlan, P.; Chambers, J.; Uhlemann, S.; Sorensen, J.; Binley, A.
ABSTRACT: In the past several decades, there has been considerable interest in groundwater–surface water interactions and their ability to regulate and cycle nutrients and pollutants. These interactions are spatially and temporally complex, but electrical resistivity imaging can be a useful tool for their characterization. Here, an electrical resistivity imaging monitoring array was installed laterally across a groundwater‐dominated Chalk river and into the adjacent riparian wetland; data were collected over a period of 1 year. Independent inversions of data from the entire transect were performed to account for the changing river stage and river water conductivity. Additionally, data from just the riparian zone were inverted using a temporally constrained inversion, and the correlation between the riparian zone resistivity patterns and river stage was assessed using time‐series analysis. The river stage and the Chalk groundwater level followed similar patterns throughout the year, and both exhibited a sharp drop following cutting of in‐stream vegetation. For the independent inversions, fixing the river resistivity led to artifacts, which prevented reliable interpretation of dynamics in the riverbed. However, the resistivity structure of the riparian zone coincided well with the intrusively derived boundary between the peat and the gravel present at the field site. Time‐series analysis of the inverted riparian zone models permitted identification of seven units with distinct hydrological resistivity dynamics (five zones within the peat and two within the gravel). The resistivity patterns in the gravel were predominantly controlled by up‐welling of resistive groundwater and the down‐welling of more conductive peat waters following the river vegetation cutting event. In comparison, although the vegetation cutting influenced the resistivity dynamics in the peat zones, the resistivity dynamics were also influenced by precipitation events and increasing pore‐water conductivity, likely arising from biological processes. It is evident that such approaches combining electrical resistivity imaging and time‐series analysis are useful for understanding the spatial extent and timing of hydrological processes to aid in the better characterization of groundwater‐surface water interactions.